Closing Sysco: Industrial Decline in Atlantic Canada's Steel City - MacKinnon, Lachlan (Studies in Atlantic Canada history, 2020)
This book is a history of deindustrialization and working-class resistance in the Cape Breton steel industry between 1945 and 2001. The Sydney Steel Works is at the heart of this study - having existed in tandem with Cape Breton's larger coal operations since the early twentieth century. Chapters explore the multi-faceted nature of deindustrialization, the internal politics of the steelworkers' union, successful efforts to nationalize the mill in 1967, the years in transition under public ownership, and confrontations over health, safety, and environmental degradation in the 1990s and 2000s. The book moves beyond the moment of closure to trace the cultural, historical, and political ramifications of deindustrialization as they continue to play out in post-industrial Cape Breton Island. This represents a significant intervention into the international literature on deindustrialization, pushing scholarship beyond the bounds of political economy and cultural change to begin tackling issues of bodily health, environment, and historical memory in post-industrial places. -- Publisher's description
Keywords: 1900-1999; Acier Industrie et commerce Nouvelle-Écosse Sydney Histoire 20e siècle; Acier Industrie et commerce Nouvelle-Écosse Sydney Personnel Conditions sociales 20e siècle; Deindustrialization; Deindustrialization Nova Scotia Sydney History 20th century; Deindustrialization Social aspects; Deindustrialization Social aspects Nova Scotia Sydney; Désindustrialisation Aspect social Nouvelle-Écosse Sydney; Désindustrialisation Nouvelle-Écosse Sydney Histoire 20e siècle; History; Nova Scotia Sydney; Plant shutdowns; Plant shutdowns Nova Scotia Sydney History 20th century; Social conditions; Steel industry and trade; Steel industry and trade Nova Scotia Sydney Employees Social conditions 20th century; Steel industry and trade Nova Scotia Sydney History 20th century; Sydney (N.-É.) Conditions sociales 20e siècle; Sydney (N.S.) Social conditions 20th century; Sydney Steel Corporation; Usines Fermeture Nouvelle-Écosse Sydney Histoire 20e siècle